Satellite observations of surface water dynamics and channel migration in the Yellow River since the 1980s - Panpan Chen; Zhigang Cao; Chen Yang; Zhiqiang Qiu; Xingjian Guo; Hongtao Duan (Journal of Hydrology: Regional Studies)
Study region: the Yellow River (YR) in China. Study focus: Due to climate change and human activities, YR channel morphology has undergone significant spatiotemporal variations. Yet, a comprehensive understanding of channel migration in YR and its driving factors remains unclear. Here, we developed a multi-index water extraction method to track the changes in surface water and river channel migration of YR based on Landsat imagery since the 1980s. New hydrological insights for the region: We find that the average surface water area of YR over the past four decades is 4013 km2, with 73.5 % of permanent surface water. Notably, the surface water extent has experienced a 9 % increase since the 1980s, while the river channel has undergone a 12.2 % decrease. The YR channel’s centerline exhibits diverse change patterns across the entire basin, which can be broadly categorized into six types ranging from unchanged to reverse migration. We identify that climate, particularly temperature and precipitation, contributed 71 % of channel changes in the upper reaches, while 65 % of changes in the lower reaches are from human activities, including reservoir operations and water management policies. Our results unveil the variations in water extent and channel migration of the YR, offering new insights into the interactions between channel migration and climate change and human activities in the YR over the past four decades.